2007
DOI: 10.1128/jb.01518-06
|View full text |Cite
|
Sign up to set email alerts
|

Specific Bonds between an Iron Oxide Surface and Outer Membrane Cytochromes MtrC and OmcA from Shewanella oneidensis MR-1

Abstract: Shewanella oneidensis MR-1 is purported to express outer membrane cytochromes (e.g., MtrC and OmcA) that transfer electrons directly to Fe(III) in a mineral during anaerobic respiration. A prerequisite for this type of reaction would be the formation of a stable bond between a cytochrome and an iron oxide surface. Atomic force microscopy (AFM) was used to detect whether a specific bond forms between a hematite (Fe 2 O 3 ) thin film, created with oxygen plasma-assisted molecular beam epitaxy, and recombinant Mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 50 publications
(70 reference statements)
3
135
0
Order By: Relevance
“…OmcA previously was thought to be only a terminal reductase of metals, which was supported by in vitro biochemical evidence that it can reduce various forms of iron (46,47,56). OmcA previously was shown to bind insoluble forms of iron in vitro with a high affinity (56), a greater affinity than that of MtrC (28). We suggest that while OmcA plays a small role in electron transfer in vivo, it also is involved in cellular attachment to solid surfaces or other cells.…”
Section: Vol 192 2010 Reduction Of Flavins and Electrodes By S Onementioning
confidence: 68%
See 1 more Smart Citation
“…OmcA previously was thought to be only a terminal reductase of metals, which was supported by in vitro biochemical evidence that it can reduce various forms of iron (46,47,56). OmcA previously was shown to bind insoluble forms of iron in vitro with a high affinity (56), a greater affinity than that of MtrC (28). We suggest that while OmcA plays a small role in electron transfer in vivo, it also is involved in cellular attachment to solid surfaces or other cells.…”
Section: Vol 192 2010 Reduction Of Flavins and Electrodes By S Onementioning
confidence: 68%
“…Strains lacking the genes omcA (⌬omcA), mtrC (⌬mtrC), mtrA (⌬mtrA), and mtrB (⌬mtrB), as well as a strain lacking both omcA and mtrC (⌬omcA ⌬mtrC), were tested for their ability to reduce both riboflavin and FMN. Both flavins were tested here, because they have been detected previously in wild-type cultures of electrode (28) and iron-reducing cultures (49) of S. oneidensis strain MR-1. Quantitative RT-PCR confirmed that in all constructed mutants, the expression of the remaining mtr genes was not altered more than twofold compared to that of the wild type (see Table S1 in the supplemental material).…”
Section: Flavin Reduction By Mtr Mutantsmentioning
confidence: 99%
“…Microscopic imaging of cell exteriors labeled with an MtrC-specific antibody showed surface-exposed MtrC colocalized with cell-associated iron precipitates (15). It also has been reported that purified MtrC can bind tightly to hematite (α-Fe 2 O 3 ) (16). In support of electron transfer by direct contact, studies of S. oneidensis grown on an Fe(III) oxyhydroxide mineral surface showed the bacterial cells were associated with Fe(II)-enriched areas (17).…”
mentioning
confidence: 88%
“…To determine if MtrA was expressed in each mutant, we attached a His 6 tag at the C terminus of MtrA to facilitate protein detection (see Table S1 in the supplemental material). Previous studies have successfully expressed correctly folded and functional multiheme cytochromes MtrC and MtrA carrying a C-terminal His 6 tag in E. coli and Shewanella MR-1 (14,27,28). MtrA could be detected in soluble preparations from cells grown anaerobically with fumarate and lactate.…”
Section: Reduction Of Terminal Electron Acceptorsmentioning
confidence: 99%